Knowledge and practice of breast self-examination among women of reproductive age group in Palakkad district of Kerala: a cross-sectional study - P. A., Raseena; Suresh, Salabha Sindhu; Pushparani, Joy Patricia; M., Jeshela; A. S., Nada Parveen; Chandran, Athira T. (International Journal Of Community Medicine And Public Health, 2025)
Background: In India, non-communicable diseases (NCDs) are estimated to be 63% of all deaths, and cancer is one of the leading causes (9%). In 2022, there were 2.3 million women diagnosed with breast cancer and 670,000 deaths globally. Breast cancer mortality rates are primarily due to inadequate knowledge about the disease's risk factors, warning signals, and breast self-examination (BSE). Methods: A Hospital-based cross-sectional survey was conducted among 106 reproductive age group women excluding those diagnosed with breast cancer by nonprobability sampling. A structured questionnaire was used to assess the knowledge of breast cancer and BSE. Data was analyzed using SPSS 20 with inferential statistics using chi-square test. Results: Breast cancer knowledge was good in 70 (66%). 79 (74.5%) of the respondents had heard about BSE and out of them only 31 (29.2%) of respondents had practiced BSE. Not knowing the correct method was the most frequently reported reason for non-performance in 59 (55.7%). Only 8 (7.5%) of the women had received information about breast cancer from health professionals while a majority 53 (50%) stated that their source of information was family and friends. Higher educational level was found to be significantly associated with knowledge of breast cancer (p=0.003). A significant association was observed between knowledge and practice of BSE. (p=0.003). Conclusions: A two third of the Participants had good knowledge of breast cancer; however, the practice of BSE is still lacking. Therefore, BSE practice needs to be promoted among women for early detection of breast cancer and prompt management.